2021
DOI: 10.1177/00224669211065051
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Disabilities in Sierra Leone

Abstract: Most disability research originates from high-income countries, masking important cultural variability in how disability is conceptualized. Through 199 interviews with people living in Sierra Leone, we investigated the following research questions: (1) what are the experiences of community members with people with disabilities?; (2) what employment options or other resources are available for people with disabilities?; and (3) how do community members perceive people with disabilities? We used a mixed-method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Furthermore, very few studies focused on emotional and behavior disorders, autism spectrum disorder, attention deficit hyperactivity disorder, specific learning disabilities, developmental disabilities, and traumatic brain injury, indicating a lack of understanding of these types of disabilities. This finding corroborates prior research that found disabilities in Western Africa are often understood according to the dichotomous categorization of “physical” or “mental” (Morin et al, 2021), with less known about other types of disabilities. As such, it is possible that studies describing participants as “mentally ill” or “crazy” were referring to people, not with mental health disorders as they are understood in the Western world, but instead with disabilities such as autism, attention-deficit hyperactivity disorder, emotional and behavior disorders, and others that are not as well known in Western Africa.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, very few studies focused on emotional and behavior disorders, autism spectrum disorder, attention deficit hyperactivity disorder, specific learning disabilities, developmental disabilities, and traumatic brain injury, indicating a lack of understanding of these types of disabilities. This finding corroborates prior research that found disabilities in Western Africa are often understood according to the dichotomous categorization of “physical” or “mental” (Morin et al, 2021), with less known about other types of disabilities. As such, it is possible that studies describing participants as “mentally ill” or “crazy” were referring to people, not with mental health disorders as they are understood in the Western world, but instead with disabilities such as autism, attention-deficit hyperactivity disorder, emotional and behavior disorders, and others that are not as well known in Western Africa.…”
Section: Discussionsupporting
confidence: 91%
“…This finding supports previous reviews that found disabilities that are not readily apparent based on a person’s outward appearance, such as autism spectrum disorder, were rarely studied in sub-Saharan Africa (Franz et al, 2017). Mental health disorders were the focus of the largest number of studies; however, many studies referred to individuals with this disability as being “mentally ill” or “crazy,” demonstrating the intense stigma surrounding disabilities that are understood differently in Western Africa (see Baffoe, 2013; Morin et al, 2021). Furthermore, very few studies focused on emotional and behavior disorders, autism spectrum disorder, attention deficit hyperactivity disorder, specific learning disabilities, developmental disabilities, and traumatic brain injury, indicating a lack of understanding of these types of disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations